Influência da adição de biopolímeros e hidroxiapatita em pastas de cimento contendo sílica para cimentação de poços de petróleo - Santos, Ivory Marcos Gomes dos (2017)
Portland cement pastes are applied in the cementing of oil wells in sedimentary saliferous basins in regions called Pre-Salt. Usually, silica amounts are added to cement slurries to reduce portlandite formation, what increases the chemical reactivity of cemented regions before chemical attacks. However, little is known about the application of other types of materials, such as natural polymers, for example chitosan and sodium alginate, and hydroxyapatite, which can be extracted from fish scales. The influence of the addition of hydroxyapatite from fish scales, chitosan and sodium alginate in silica-containing cement pastes, which were prepared and hydrated with sea water, was evaluated in this study. After 28 days of hydration at room temperature, it was observed that the cement paste prepared only with silica exhibited a higher percentage of portlandite compared to that prepared with hydroxyapatite, chitosan and sodium alginate. These cement pastes were evaluated before solutions of sodium chloride (NaCl), sulfuric acid (H2SO4), as well as in production water under different experimental conditions. The results indicated that in cement pastes were still anhydrous compounds, which had not been hydrated. Thus, the cement pastes continued to be hydrated during the immersion tests. In the analysis, it was observed that the paste prepared with hydroxyapatite, chitosan and sodium alginate, showed to be more resistant in presence of the chemical attacks, due to having smaller amounts of portlandite.